2005
DOI: 10.1073/pnas.0505641102
|View full text |Cite
|
Sign up to set email alerts
|

Atypical PKCι contributes to poor prognosis through loss of apical-basal polarity and Cyclin E overexpression in ovarian cancer

Abstract: We show that atypical PKCiota, which plays a critical role in the establishment and maintenance of epithelial cell polarity, is genomically amplified and overexpressed in serous epithelial ovarian cancers. Furthermore, PKCiota protein is markedly increased or mislocalized in all serous ovarian cancers. An increased PKCiota DNA copy number is associated with decreased progression-free survival in serous epithelial ovarian cancers. In a Drosophila in vivo epithelial tissue model, overexpression of persistently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
223
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(241 citation statements)
references
References 41 publications
16
223
2
Order By: Relevance
“…Translocation of activated PKCε to the membrane upon TPA treatment has been shown in other studies [42,55] and alteration of TJs by translocation of PKCε has been shown previously in epithelial cells [42]. Various isoforms of PKC have been implicated in ovarian tumorigenesis and drug resistance [56][57][58][59][60][61][62]. Involvement of PKCε in tumor development, invasion, and metastasis have been shown in other tissues [50,[63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 91%
“…Translocation of activated PKCε to the membrane upon TPA treatment has been shown in other studies [42,55] and alteration of TJs by translocation of PKCε has been shown previously in epithelial cells [42]. Various isoforms of PKC have been implicated in ovarian tumorigenesis and drug resistance [56][57][58][59][60][61][62]. Involvement of PKCε in tumor development, invasion, and metastasis have been shown in other tissues [50,[63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 91%
“…Subsequent interaction of PAR1 with 14-3-3 dissociates PAR1 from the plasma membrane, thereby preventing the distribution of PAR1 to the apical membrane domain. Gene amplification and elevated activity of aPKC, which downregulates PAR1 functions, have also been reported in ovarian, lung and colon carcinomas (Murray et al, 2004;Eder et al, 2005;Regala et al, 2005).…”
Section: Function Of Par1 In Carcinogenesismentioning
confidence: 92%
“…Gene amplification and elevated constitutive activity of aPKC has been correlated with poor prognosis in ovarian, lung and colon cancer, suggesting that this protein may behave as an oncogene (Murray et al, 2004;Eder et al, 2005;Regala et al, 2005a, b). Tumors with elevated levels of aPKC display loss of polarity, in agreement with the known role of this kinase in regulating epithelial polarity at normal expression levels.…”
Section: Hijacking Of the Domain-identity Machinerymentioning
confidence: 99%